Recovery from cold-induced mitochondrial fission in endothelial cells requires reconditioning temperatures of ≥ 25◦C - Quiring, Leonard; Caponi, Luisa; Schwan, Dhanusha; Rech, Anja; Rauen, Ursula (Frontiers in Transplantation, 2022)
Mitochondrial integrity and function constitute a prerequisite for cellular function and repair processes. We have previously shown that mitochondria of different cell types exhibit pronounced fragmentation under hypothermic conditions. This fission, accompanied by a decline of cellular ATP content, showed reversibility at 37 °C. However, it is unclear whether other temperatures as currently discussed for reconditioning of organs allow this reconstitution of mitochondria. Therefore, we here study in a model of cultured porcine aortic endothelial cells how different rewarming temperatures affect mitochondrial re-fusion and function. After 48 h cold incubation of endothelial cells in Krebs-Henseleit buffer with glucose (5 mM) and deferoxamine (1 mM) at 4 °C pronounced mitochondrial fission was observed. Following 2 h rewarming in cell culture medium, marked fission was still present after rewarming at 10 or 15 °C. At 21 °C some re-fusion was visible, which became more marked at 25 °C. Networks of tubular mitochondria similar to control cells only re-appeared at 37 °C. ATP content decreased at 4 °C from 3.6 ± 0.3 to 1.8 ± 0.6 nmol/10^6 cells and decreased even further when rewarming cells to 10 and 15 °C. Values after rewarming at 21 °C were similar to the values before rewarming while ATP gradually increased at higher rewarming temperatures. Metabolic activity dropped to 5 ± 11 % of control values during 4 °C incubation and recovered with increasing temperatures to 36 ± 13 % at 25 °C and 77 ± 17 % at 37 °C. Integrity of monolayers, largely disturbed at 4 °C (large gaps between endothelial cells; cell injury ≤ 1 %), showed partial recovery from 15 °C upwards, complete recovery at 37 °C. Endothelial repair processes (scratch assay) at 25 °C were clearly inferior to those at 37 °C. These data suggest that reconditioning temperatures below 21 °C are not optimal with regard to reconstitution of mitochondrial integrity and function. For this goal, temperatures of at least 25 °C appear required, with 30 °C being superior and 37 °C yielding the best results.